Comparative Ultrasonographic Assessment of Splenic Length in NonPregnant and Pregnant Women: - Yadav, Subodh; Yadav, Renu; Yadav, Anil; Karn, Abhishek (Nepal Journal of Health Sciences, 2026)
Introduction: The spleen is the largest lymphatic organ of the reticuloendothelial and lymphatic systems and plays a crucial role in immune function and blood filtration. During pregnancy, increased blood volume and altered hemodynamics represent normal physiological changes that lead to an increase in spleen size. However, limited data are available regarding trimester-wise changes in splenic dimensions during normal pregnancy. Methods: This comparative cross-sectional descriptive study was conducted in the Department of Radiology at Birat Medical College and Teaching Hospital, over a two-month period. 200 healthy women were included, comprising 150 pregnant women (50 in each trimester) and 50 age and height matched non-pregnant controls. Splenic length was measured using a 3.5 MHz curvilinear transducer, with participants positioned supine or in the right lateral decubitus position as required. Descriptive and comparative analysis were performed using SPSS version 24. Results: This study showed the mean splenic length in non-pregnant women as 96.60 ± 7.40 mm whereas 94.20 ± 7.60 mm, 99.0 ± 7.50 mm, and 106.20 ± 7.80 mm for pregnant women of 1st, 2nd and 3rd trimesters. Statistically significant increment in splenic length in women were noted, comparing control with 3rd trimester (p <0.001), 1st with 2nd trimesters (p=0.01), 1st with 3rd trimesters (p < 0.001), and 2nd with 3rd trimesters (p <0.001). There was non-significant difference observed comparing control with 1st (p=0.39) and 2nd (p=0.39) trimester of pregnancy. Conclusions: Splenic length increases progressively with advancing gestation, especially in the second and third trimesters, reflecting normal physiological adaptations of pregnancy rather than pathology.